Part 7: Systems of Care. Issue 16 (20th October 2020) - Berg, Katherine M.; Cheng, Adam; Panchal, Ashish R.; Topjian, Alexis A.; Aziz, Khalid; Bhanji, Farhan; Bigham, Blair L.; Hirsch, Karen G.; Hoover, Amber V.; Kurz, Michael C.; Levy, Arielle; Lin, Yiqun; et al.
Abstract : Survival after cardiac arrest requires an integrated system of people, training, equipment, and organizations working together to achieve a common goal. Part 7 of the 2020 American Heart Association Guidelines for Cardiopulmonary Resuscitation and Emergency Cardiovascular Care focuses on systems of care, with an emphasis on elements that are relevant to a broad range of resuscitation situations. Previous systems of care guidelines have identified a Chain of Survival, beginning with prevention and early identification of cardiac arrest and proceeding through resuscitation to post–cardiac arrest care. This concept is reinforced by the addition of recovery as an important stage in cardiac arrest survival. Debriefing and other quality improvement strategies were previously mentioned and are now emphasized. Specific to out-of-hospital cardiac arrest, this Part contains recommendations about community initiatives to promote cardiac arrest recognition, cardiopulmonary resuscitation, public access defibrillation, mobile phone technologies to summon first responders, and an enhanced role for emergency telecommunicators. Germane to in-hospital cardiac arrest are recommendations about the recognition and stabilization of hospital patients at risk for developing cardiac arrest. This Part also includes recommendations about clinical debriefing, transport to specialized cardiac arrest centers, organ donation, and performance measurement across the continuum of resuscitation situations.